Expanded roles of leucine-responsive regulatory protein in transcription regulation of the Escherichia coli genome: Genomic SELEX screening of the regulation targets. Issue 1 (15th July 2015) - Shimada, Tomohiro; Saito, Natsumi; Maeda, Michihisa; Tanaka, Kan; Ishihama, Akira
Abstract : Leucine-responsive regulatory protein (Lrp) is a transcriptional regulator for the genes involved in transport, biosynthesis and catabolism of amino acids in Escherichia coli . In order to identify the whole set of genes under the direct control of Lrp, we performed Genomic SELEX screening and identified a total of 314 Lrp-binding sites on the E. coli genome. As a result, the regulation target of Lrp was predicted to expand from the hitherto identified genes for amino acid metabolism to a set of novel target genes for utilization of amino acids for protein synthesis, including tRNAs, aminoacyl-tRNA synthases and rRNAs. Northern blot analysis indicated alteration of mRNA levels for at least some novel targets, including the aminoacyl-tRNA synthetase genes. Phenotype MicroArray of the lrp mutant indicated significant alteration in utilization of amino acids and peptides, whilst metabolome analysis showed variations in the concentration of amino acids in the lrp mutant. From these two datasets we realized a reverse correlation between amino acid levels and cell growth rate: fast-growing cells contain low-level amino acids, whilst a high level of amino acids exists in slow-growing cells. Taken together, we propose that Lrp is a global regulator of transcription of a large number of the genes involved in not only amino acid transport and metabolism, but also amino acid utilization.